2023
DOI: 10.1111/cts.13598
|View full text |Cite
|
Sign up to set email alerts
|

Keverprazan, a novel potassium‐competitive acid blocker: Multiple oral doses safety, tolerability, pharmacokinetics, and pharmacodynamics in healthy subjects

Abstract: Keverprazan, a novel potassium‐competitive acid blocker, was approved for treating acid‐related diseases. This study aimed to analyze the safety, pharmacokinetics (PKs) and pharmacodynamics (PDs) of multiple doses of keverprazan. This was a randomized, positive‐/placebo‐controlled, phase Ic trial. Twenty‐six healthy adults were randomized to receive 20 mg/day keverprazan (n = 8), 40 mg/day keverprazan (n = 8), placebo (n = 6), or 20 mg/day vonoprazan (n = 4) for 7 days. Safety, PK and PD assessments were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…It was designed based on the structure of Vonoprazan and has a high distribution in the stomach, providing better control of stomach acid. 73 A published clinical trial (ChiCTR2100050136) indicated that the percentages of time of intragastric pH greater than 4 [pH >4 holding-time ratio (HTR)] in Placebo, 20 mg Vonoprazan, and 20 mg Keverprazan groups were 5.6 ± 2.4%, 82.2 ± 12.6%, and 85.0 ± 3.0% on day 1, respectively, and the corresponding night-time HTR values were 3.9 ± 4.7%, 87.9 ± 15.7%, and 99.9 ± 0.0%, respectively. 67 Another phase I study showed that starting 4 h after administration, the pH levels in the 20–60 mg dose groups of Keverprazan were consistently higher than those in the 30 mg Lansoprazole group.…”
Section: Discussionmentioning
confidence: 99%
“…It was designed based on the structure of Vonoprazan and has a high distribution in the stomach, providing better control of stomach acid. 73 A published clinical trial (ChiCTR2100050136) indicated that the percentages of time of intragastric pH greater than 4 [pH >4 holding-time ratio (HTR)] in Placebo, 20 mg Vonoprazan, and 20 mg Keverprazan groups were 5.6 ± 2.4%, 82.2 ± 12.6%, and 85.0 ± 3.0% on day 1, respectively, and the corresponding night-time HTR values were 3.9 ± 4.7%, 87.9 ± 15.7%, and 99.9 ± 0.0%, respectively. 67 Another phase I study showed that starting 4 h after administration, the pH levels in the 20–60 mg dose groups of Keverprazan were consistently higher than those in the 30 mg Lansoprazole group.…”
Section: Discussionmentioning
confidence: 99%
“…Keverprazan was approved in China in February 2023 [ 16 ]. Based on the structure of vonoprazan, keverprazan changes the pyridine into a benzene ring with an ether chain, altering its lipid solubility, enhancing its water solubility, and thereby changing its tissue distribution, particularly increasing its distribution in the target organ [ 78 ]. Consequently, it also achieves a good acid inhibition effect.…”
Section: Discussionmentioning
confidence: 99%